Pelatihan Praktis Menggunakan Aplikasi Spreadsheet untuk Pembuatan dan Pengelolaan Nilai Raport - Linda Santiari, Ni Putu; I Putu Ramayasa; I Wayan Kayun Suwastika; I Gede Surya Rahayuda (Insan Kreasi Media, 2023)
Training on optimizing number processing applications for creating and inputting report cards at Bina Madina Denpasar Vocational School is an initiative aimed at improving teachers' skills in effectively utilizing spreadsheet applications. This training began with socialization activities which included presenting the training objectives, opening a space for dialogue to evaluate participants' expectations, and conveying the training schedule and materials. The training process includes presentation sessions, demonstrations and practical exercises, focusing on optimizing the use of number processing applications to compile and manage report cards efficiently. Evaluation is carried out to measure participants' understanding, involving written exams, reflection sessions, and satisfaction questionnaires. Monitoring is carried out post-training to monitor the application of participants' skills in daily activities, with analysis of report card results, online monitoring sessions, and ongoing evaluation. This training aims to create a modern and efficient learning environment, ensure that teachers can provide report cards accurately and effectively, and stimulate innovation in managing grades in the educational environment.